The future of nonprofits : innovate and thrive in the digital age - Neff, David J., 1977-; Moss, Randal C., 1977- (Hoboken, N.J. : John Wiley & Sons, 2011)
'How nonprofits can successfully leverage internal innovation programs and future trends to grow revenue and drive their mission The Future of Nonprofits helps organizations capitalize on their ability to innovate and predict future trends to remake and reshape their culture, structure, and staff to be more nimble and lean organizations. By applying the strategies and tactics laid out in this book, nonprofit professionals of all levels can prepare their organizations to take advantage of future trends and develop innovative'internal entrepreneurs' that will grow revenue and drive their mission. Provides nonprofits with a comprehensive playbook on how to create a new, more flexible, innovative organization Provides nonprofits a look at the future of fundraising and communications trends into 2016 Case studies highlight successes and failures of non profit innovation in the digital media space Highlights the power and strength of Social Media Features actionable advice on creating an organization that is primed to grow and thrive in the immediate future and over the long-term This game-changing book reveals how every nonprofit can put technology, innovation, and future trends to work to reach their mission and grow revenue'--
Includes bibliographical and index.
Keywords: Nonprofit organizations -- Management; Nonprofit organizations -- Management -- Case studies